ANTIDIABETES ACTIVITIES EXTRACT HEXANE FROM THE PEELS OF ARTOCARPUS CAMANSI BLANCO FRUIT - Nasution, Rosnani; Nur Fitrah, Chairani; Helwati, Hira; Murniana, Murniana; Arifin, Bastian; Cutchamzurni, Cutchamzurni; Rizal, Yose; Marianne, Marianne (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The purpose of this research is to know the chemical compound from the n-hexane extract of Kulu (Artocarpus camansi Blanco) fruit peels and to know its antidiabetes activity against male Swiss Webster mice. Methods: Samples were macerated with n-hexane solvent, then the extracts were obtained, was characterization with gas chromatography-mass spectrometry (GC-MS), and then the extract separated by column chromatography. The results obtained were tested by antidiabetes action with glucose tolerance method. Results: Anti-diabetic activity test result showed that the most active sample to decrease the blood glucose of mice was n-hexane crude extract, at minute 90th, activeness was 65.59%, compared to glibenclamide, then group of fraction A, at minute 90th, activeness 65.58% compared glibenclamide, whereas isolate D11, its activity is 60.11% and 60.12%, at minute 60th and 90 min compared to glibenclamide. Concentrated extracts were characterized by GC-MS, shows the major compounds are hexadecanoic acid methyl ester (30.14%), 9,12-octadecadienoyl chloride, (Z, Z) - (8.44%) and 9-octadecenoic acid, methyl ester (30,91%) also were obtained a compound like an Î²-amyrin acetate. Conclusion: The most active sample to decrease the blood glucose of mice was n-hexane crude extract, and the major compounds are hexadecanoic acid methyl ester (30.14%), 9,12-octadecadienoyl chloride, (Z, Z) - (8.44%) and 9-octadecenoic acid, methyl ester (30.91%).